2002
DOI: 10.1074/jbc.m205000200
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Serine Hydroxymethyltransferase Mediates Competition between Folate-dependent Deoxyribonucleotide andS-Adenosylmethionine Biosyntheses

Abstract: Folate-dependent one-carbon metabolism is required for the synthesis of purines and thymidylate and for the remethylation of homocysteine to methionine. Methionine is subsequently adenylated to S-adenosylmethionine (SAM), a cofactor that methylates DNA, RNA, proteins, and many metabolites. Previous experimental and theoretical modeling studies have indicated that folate cofactors are limiting for cytoplasmic folate-dependent reactions and that the synthesis of DNA precursors competes with SAM synthesis. Each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
252
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 247 publications
(281 citation statements)
references
References 33 publications
15
252
2
1
Order By: Relevance
“…Previous studies have demonstrated that SHMT1 activity is the rate-limiting activity in thymidylate biosynthesis in MCF-7 cells. Overexpression of SHMT1 in MCF-7 cells not only favors the partitioning of folate-derived one-carbon units to thymidylate biosynthesis but also enhances the efficiency of de novo thymidylate biosynthesis relative to synthesis through the salvage pathway (11). Unlike the other enzymes involved in folate-mediated one-carbon metabolism, SHMT1 expression is not ubiquitous.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have demonstrated that SHMT1 activity is the rate-limiting activity in thymidylate biosynthesis in MCF-7 cells. Overexpression of SHMT1 in MCF-7 cells not only favors the partitioning of folate-derived one-carbon units to thymidylate biosynthesis but also enhances the efficiency of de novo thymidylate biosynthesis relative to synthesis through the salvage pathway (11). Unlike the other enzymes involved in folate-mediated one-carbon metabolism, SHMT1 expression is not ubiquitous.…”
Section: Discussionmentioning
confidence: 96%
“…To date, we have not detected significant changes in the levels of mRNA expression of several folate pathway genes in Hoxd4 transgenic chondrocytes (Kruger, Talmadge and Kappen, unpublished data) leaving the mechanistic targets for folate supplementation in transgenic chondrocytes as of yet unidentified. We show that chondrocytes need folate specifically for proliferation and differentiation, and the levels of cellular folate metabolites are known to control the balance between DNA synthesis and methylation of DNA and proteins (Herbig et al, 2002). Altered DNA methylation (Bird, 2002) or histone methylation (Lachner and Jenuwein, 2002) may affect the activity of genes regulated by Hox transcription factors, but this remains speculation until such downstream targets -of either Hox genes or folate -have been identified in skeletal cells.…”
Section: Discussion Folate Restores Skeletal Defects In Hox Transgenimentioning
confidence: 99%
“…For example, the enzymes affecting folate catabolism 37 or methylene-THF synthesis might be of importance. 38,39 Similarly, the mitochondrial counterpart of MTHFD1, the NAD-dependent methylenetetrahydrofolate dehydrogenase, can influence 10-formyl-THF generation that in turn contributes to the cytoplasmatic folate pools. 40 In order to analyze the whole range of polymorphisms underlying other enzymatic variants within the folate pathway, as well as their possible gene-gene interactions, it is necessary that much larger and more collaborative studies be undertaken, if we are to understand the role of gene polymorphisms in ALL outcome.…”
Section: Dfs But Not Os)mentioning
confidence: 99%